2019
DOI: 10.1073/pnas.1813020116
|View full text |Cite
|
Sign up to set email alerts
|

The mucin-selective protease StcE enables molecular and functional analysis of human cancer-associated mucins

Abstract: Mucin domains are densely O-glycosylated modular protein domains that are found in a wide variety of cell surface and secreted proteins. Mucin-domain glycoproteins are known to be key players in a host of human diseases, especially cancer, wherein mucin expression and glycosylation patterns are altered. Mucin biology has been difficult to study at the molecular level, in part, because methods to manipulate and structurally characterize mucin domains are lacking. Here, we demonstrate that secreted protease of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
315
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 224 publications
(328 citation statements)
references
References 81 publications
13
315
0
Order By: Relevance
“…To assess labeling specificity, we also tested glycoprotein susceptibility towards hydrolytic enzymes. We treated samples with the mucinase StcE that specifically digests highly O-GalNAcylated mucin domains, or with sialidase that removes sialic acid from glycoconjugates (36). Following StcE treatment, the most intense bands labeled by both caged GalNAzMe-1-phosphate 11 and Ac 4 GalNAz feeding had disappeared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess labeling specificity, we also tested glycoprotein susceptibility towards hydrolytic enzymes. We treated samples with the mucinase StcE that specifically digests highly O-GalNAcylated mucin domains, or with sialidase that removes sialic acid from glycoconjugates (36). Following StcE treatment, the most intense bands labeled by both caged GalNAzMe-1-phosphate 11 and Ac 4 GalNAz feeding had disappeared.…”
Section: Resultsmentioning
confidence: 99%
“…Supernatant was transferred to a new plate and BCA was used to measure protein concentration. For enzyme treatment, equal amounts of protein (typically 15 µg) were diluted to 40 µL with Lysis Buffer or PBS, treated with either SialEXO (4 µL of a 4 U/µL solution in 50 mM Tris-HCl (pH 6.5), Genovis, Lund, Sweden) or the glycoprotease StcE (50 nM in PBS) (19) and incubated for 2 h at 37 °C. The reaction was quenched by heating to 95 °C for 10 s with subsequent cooling at 4 °C.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Empowered by the proximity labeling approach, we now have generated a priority list of proteins that will be the subject of future work to further reveal the "professional glycoprotein ligands" [14] required for the functional activation of HSCs. Already, preliminary work has shown that basigin plays an active role in hepatic fibrosis [45], and our own work will delve deeper into the molecular nature of the galectin-3-basigin interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The era of quantitative biology demands great specificity in tools to probe cellular processes or expressed antigens. Biological tools, including antibodies, lectins, engineered binding proteins, or 10 silenced hydrolases have been employed to profile or isolate cellular glycans (45,50). While powerful probes, these proteins suffer from various drawbacks, including the dependence of binding on the structural context or the requirement to simplify glycans before performing binding studies.…”
Section: Discussionmentioning
confidence: 99%